2013
DOI: 10.1007/s00432-013-1474-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical role of small glutamine-rich tetratricopeptide repeat (TPR)-containing protein alpha (SGTA) as a novel cell cycle protein in NSCLC

Abstract: These findings suggested that SGTA might play an important role in promoting the tumorigenesis of NSCLC, and thus be a promising therapeutic target to prevent NSCLC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…7). Interestingly, several recent reports correlate increases in SGTA expression with the proliferation of several forms of cancer, although the molecular basis for this observation remains to be defined (Lu et al, 2014; Philp et al, 2013; Xue et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…7). Interestingly, several recent reports correlate increases in SGTA expression with the proliferation of several forms of cancer, although the molecular basis for this observation remains to be defined (Lu et al, 2014; Philp et al, 2013; Xue et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…SGTA is required for progress through cell division and promotes cell proliferation (Winnefeld et al 2004). Recent studies demonstrated that overexpression of SGTA was frequent in lung cancer, human hepatocellular carcinoma and esophageal squamous cell carcinoma (Xue et al 2013;Lu et al 2014;Yang et al 2014). These studies have shown a high status and implied that SGTA may play an important role in cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, SGTA contains a central tetratricopeptide repeat (TPR) domain (that can interact with the C-termini of Hsp70 and Hsp90 molecular chaperones as well as viral proteins and hormone receptors) and a glutamine rich region towards the C-terminus [13]. Although all of its roles have yet to be fully elucidated, SGTA looks to be an important protein for health and disease, recently found to be up-regulated in certain cancers (oesophageal [14], liver [15], ovarian [16] and lung [17]). Recent studies of SGTA, and its yeast homologue Sgt2, have demonstrated that SGTA interacts with the BAG6 complex's two ubiquitin-like (UBL) domains via a ubiquitin-like binding domain (UBD).…”
Section: Introductionmentioning
confidence: 99%